Penguatan Peran Ekonomi Islam Melalui Optimalisasi Pembiayaan pada Sektor Riil UMKM - Trimulato Trimulato; Ismawati Ismawati; Amiruddin K; Nuraeni Nuraeni (Universitas Islam Lamongan, 2020)
Islamic economic in Indonesia continues to experience very rapid growth, seen by the increasing number of institutions operating in sharia principles, in addition to the growing and developing businesses with sharia principles. The development of the Islamic economy is inseparable from the role of various parties who continue to try to socialize the Islamic economy to society. The government seems to be very serious in supporting the development of the Islamic economy in Indonesia. It looks at the Islamic financial market share that has not enough 10 percent, so it requires more efforts for its development. It needs to determine the direction and focus on particular segments to develop so they can compete globally. The right segment chosen for the Islamic economy is the development of SMEs, given that it grows and develops in Indonesia. This study aims to find out the development of SMEs and map the strengthening of the Islamic economy through financing for SMEs. The type of research is library research and is qualitative. Data collection techniques used are through retrieval data has been there before. The data analysis technique used is descriptive qualitative, related to the development SMEs and Islamic economic institutions. Results showed that development in 2018 SMEs experienced growth, medium-sized businesses grew by 3.54 percent, and small businesses grew by 3.44 percent, while the largest portion of SMEs was microbusinesses, which amounted to 98.7 percent. Distribution financing sharia banking is still dominated by consumer consumption rather than productive. Islamic economic institutions are experiencing growth, so they can be directed to develop SMEs. Strengthening it can be done by selecting certain segments that are the focus is SMEs. The concept of profit-sharing inherent in Islamic economic transactions is very relevant to the development of SMEs. Keywords: Islamic economic; financing; SMEs